The de Lange syndrome in one of twins. - Carakushannsky, G (1976)
A pair of female monozygotic twins, one of them affected by the de Lange syndrome is described for the first time. Monozygosity was established by most of the accepted standards in use at the present time. Speculation is offered as to whether the discordance in the manifestation of the syndrome provides any clues for understanding its controversial pathogenesis. In this regard two genetic mechanisms are discussed. One is the hypothesis of a chromosomal or mitotic instability. The other possibility would be a postzygotic new mutation of a gene or large effect.